A Discounting Framework for Choice With Delayed and Probabilistic Rewards. (Articles]. - Green, Leonard
When choosing between delayed or uncertain outcomes, individual discount the value of such outcomes on the basis of the expected time or likelihood of their occurence. In an integrative review of the expanding experimental literature on discounting, the authors show that although the same form of hyperbola-like function discribe discounting of both delayed and probabilistic outcomes, a variety of recent findings are inconsistent with a single-process account. athe authors also review studies that compare discounting in different populations and discuss the theoretical and practical implications of the findings. The present effort illustrates the value of studying choice involving both delayed and probabilistic outcomes within a general discounting framework that uses similar experimental procedures and a common analytical approach.-- ( from the author)